The Influence Of Social Media Promotion On By Good Lips Product Purchase Decisions - Asep Sugara; MD. Sukamto; Nabila Liana Putri (EMaBi: Ekonomi Dan Manajemen Bisnis, 2022)
The purpose of carrying out this research is to find out how the influence of social media promotions on purchasing decisions? The research analysis approach used is a quantitative approach with associative methods. The research sample size is 100 respondents. The data collection technique used was a questionnaire distributed to social media followers by Good Lips. The results of the study show that the coefficient of determination is 71.5%, which means that the higher the social media promotion, the greater the influence on the buyer's purchasing decision to buy By good lips products. The results of the product moment correlation analysis are 0.847 which can be seen from the correlation coefficient numbers calculated using the interpretation of the r value > 0.75 – 0.99: Very strong correlation. Judging from the results of the t test, which has a t-count value of 15,786 with a Sig. 0.000. where the t table value for this research is 1,987 and the sig value > 0.05 so it can be concluded that H0 is rejected and Ha is accepted